A case report of lymphangioma circumscriptum of scrotum along with milky urethral discharge - Soomro, Naeem Ahmed; Kumari, Rakhi; Shaikh, Irfan Ahmed; Khan, Kaiser; Ahuja, Dileep Kumar; Ahmed, Sirajuddin (Journal of Pakistan Association of Dermatologists, 2019)
Lymphangioma Circumscriptum is a lymphatic malformation localized to skin, subcutaneous tissue and rarely muscles. It may present at any age but usually noted at birth or during childhood. It is due to malformation of lymphatic channels. We present a case of 9 years old patient of lymphangioma circumscriptum of scrotum along with milky urethral discharge. Patient was treated with oral sildenafil and CO2 Laser